Oral Infection and Survival of Trypanosoma cruzi in Sugarcane Juice Conditioned at Different Temperatures - Suzuki, Augusto Furukawa; de Souza, Ewelyn Regina; Spadella, Maria Angélica; Chagas, Eduardo Federighi Baisi; Hataka, Alessandre [UNESP]; Martins, Luciamáre Perinetti Alves (Springer Nature, 2024)
Purpose: The current most important form of transmission for Trypanosoma cruzi is the oral route, being responsible for high mortality during the acute phase in infected individuals. Thus, this study aimed to investigate the possibility of infection for this parasite using sugarcane juice in different temperatures employing metacyclic trypomastigotes obtained from xenodiagnosis performed in Swiss mice previously infected with T.cruzi Y strain, and then diluted in sugarcane juice. Methods: For stomach histopathological analysis, 20 mice were infected with metacyclic trypomastigotes diluted in sugarcane juice and euthanized after the 2nd, 4th, 10th, and 15th days after infection. Concurrently, six batches of ten mice were fed using 1.5 mL of the mixture and kept for 12 h at the temperatures of – 80 ºC, − 20 ºC, + 2 ºC, + 28 ºC, + 60 ºC, and + 80 ºC, for later infection verification. Results: Inflammatory infiltrate was found after the 2nd day of infection, and amastigotes nests were present after the 4th, 10th, and 15th day in the margo plicatus stomach region. Viable trypomastigotes were observed in the microtubes kept at – 80 ºC, − 20 ºC, and + 2 ºC, but the animal’s infection was observed in the – 80 ºC and + 2 ºC groups. In vitro tests demonstrated the decrease of T. cruzi trypomastigote viability, which was negative after 120 h at −20 ºC and 144 h at + 2 ºC, in contrast to the maintenance of survival after 168 h at – 80 ºC. Conclusion: We observed the ability of survival and infection of T. cruzi packaged at − 80 ºC without the use of preservatives and, therefore, less suitable for storing food.
Keywords: Chagas disease; Cryopreservation; Gastric absorption; Inflammation; Sugarcane; Trypanosoma cruzi